Effect of WRP and FGD gypsum on engineering properties and microstructures of HVBSM. Issue 2 (28th January 2019) - Han, Mincheol; Yi, Seong-Tae; Yoon, Weonkeun
Abstract : The objective of this study is to investigate the effect of the use of waste refractory powder (WRP) and flue gas desulfurization (FGD) gypsum as an activator on the engineering properties and microstructures of high-volume blast-furnace slag mortar (HVBSM). WRP was used as a magnesium oxide (MgO) source, and FGD gypsum as a calcium sulfate source, to activate blast-furnace slag (BS). The test results indicated that, when BS alone was used for substitution, the flow was lowered compared with that of the control mixture, while the flow increased with substitution with WRP and FGD gypsum. Under the given FGD gypsum contents, the increase in WRP resulted in increased flow. The combined replacement with WRP and FGD gypsum resulted in the enhancement of the compressive strength at the age of 28 d compared to that of the control mixture. It is believed that the activation effect of FGD gypsum on BS in this study was more apparent than that of WRP. For the microstructure observations, HVBSM incorporating WRP exhibited the formation of magnesium hydroxide. In addition, HVBSM with FGD gypsum also showed larger amounts of ettringite and monosulfate hydrate, which allow HVBSM to make denser structures.